Career Choice and Transition of Professional Interests among English Education Students - Arafiq Arafiq; Arifuddin Arifuddin; Lalu Nurtaat; Amrullah Amrullah; Hidayat Andre; Ni Nyoman Sita Laksmi (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The division of elective tracks in undergraduate education programs continues to raise concerns regarding the alignment between students’ chosen specializations and subsequent career transitions. So far, studies on career choice and professional interests transitions among English education students in elective-based classes are deficient. This study aims to identify: (1) students’ initial elective class choices, (2) their preferences across elective tracks, (3) their tendency to shift to other professions, (4) the underlying reasons for such transitions, and (5) the adequacy of credit allocation for elective courses offered. Methodology: This descriptive study involved 142 students enrolled in elective tracks. Data were collected through Google Forms and semi-structured interviews. Questionnaire data were analyzed using descriptive statistics, while interview data were examined qualitatively. Main Findings: The findings indicate that students predominantly prefer electives in tourism (47.9%) and education (42.3%), with relatively low interest in research-oriented tracks. Career choice consistency is relatively high (64.7%); however, transitions are influenced by personal, social, and professional development factors. The adequacy of credit allocation for elective courses is generally perceived positively. Novelty/Originality of this study: This study reveals a developed theoretical basis on career choice and professional interest transitions among education students in elective-based classes in non-vocational higher education. Nevertheless, gender, as one of the determining factors, has not been explored in this study.